2021
DOI: 10.3390/jcm10081760
|View full text |Cite
|
Sign up to set email alerts
|

Left Ventricle Structure and Function in Young Adults Born Very Preterm and Association with Neonatal Characteristics

Abstract: Preterm birth increases risk of cardiovascular disease and early death. A body of evidence suggests left ventricle (LV) echocardiographic alterations in children and adults born preterm. We aimed to determine if neonatal characteristics were associated with alterations in LV structure and function in preterm adults. We evaluated a cohort of 86 young adults born preterm below 30 weeks of gestation, and 85 full-term controls. We determined LV dimensions and function using tissue Doppler imaging, conventional and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 49 publications
1
8
0
Order By: Relevance
“…These reports showed either no difference, increased risk of disease for males, or increased risk for females depending on the outcome examined. 58,59 Clinical papers from our group previously showed no sex-based difference between preterm and term individuals on overall cardiovascular risk factors, on the left ventricle 20 and the right ventricle 60 and on hemoglobin levels. 61 Nevertheless, in the clinical part of our study, both men and women were evaluated and although the lack of power prevent us to perform statistical analyses of sex-stratified results, humanin serum levels were similarly lower in preterm versus term for both males and females.…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations
“…These reports showed either no difference, increased risk of disease for males, or increased risk for females depending on the outcome examined. 58,59 Clinical papers from our group previously showed no sex-based difference between preterm and term individuals on overall cardiovascular risk factors, on the left ventricle 20 and the right ventricle 60 and on hemoglobin levels. 61 Nevertheless, in the clinical part of our study, both men and women were evaluated and although the lack of power prevent us to perform statistical analyses of sex-stratified results, humanin serum levels were similarly lower in preterm versus term for both males and females.…”
Section: Discussionmentioning
confidence: 84%
“…Our results suggest that mitochondrial dysfunction is present in preterm-born adults and that these alterations may be related to left ventricular systolic function. Because left ventricle ejection fraction and left ventricle systolic deformation by speckle-tracking echocardiography were within normal range for most participants, 20 we cannot extrapolate current results to diseased states. How left ventricle systolic function in preterm individuals will evolve with aging and associated age-related risk factors, and whether serum humanin could be used to predict risk of heart disease, remain to be determined.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…Examining the records of all individuals born in Sweden between 1973 and 1994, Crump et al (9) demonstrated that gestational age is inversely correlated with the incidence of ischemic heart diseases , and that cardiometabolic changes may predispose to the development of ischemic heart disease later in life. In addition, Flahault et al (13) demonstrated that preterm birth adult survivors frequently show alterations in left ventricular structure and function markers.…”
mentioning
confidence: 99%